(untitled) (Advances in Civil and Architectural Engineering, 2022)
In previous studies, a new (improved) turboroundabout design approach based on the rules of the design vehicle movement geometry was proposed, and the optimal design of elements of standard turboroundabouts for various design vehicle scenarios, circulatory roadway radii, and approach leg positions was defined. Within the scope of this research, the applicability of the current Dutch calculation model for fastest-path vehicle speed analyses at standard turboroundabout schemes designed by a previously described procedure was examined. Research results have shown that this Dutch calculation model does not apply to standard turboroundabouts whose approach legs are aligned under various angles and translatory shifted regarding the roundabout geometric center, and therefore, should not be used for speed analyses at this roundabout type until a new calculation model, which corresponds to the real traffic situation, is developed.